Sarcoidosis: Updates on therapeutic drug trials and novel treatment approaches - Obi, Ogugua Ndili; Saketkoo, Lesley Ann; Russell, Anne-Marie; Baughman, Robert P. (Frontiers in Medicine, 2022)
Sarcoidosis is a systemic granulomatous inflammatory disease of unknown etiology. It affects the lungs in over 90% of patients yet extra-pulmonary and multi-organ involvement is common. Spontaneous remission of disease occurs commonly, nonetheless, over 50% of patients will require treatment and up to 30% of patients will develop a chronic progressive non-remitting disease with marked pulmonary fibrosis leading to significant morbidity and death. Guidelines outlining an immunosuppressive treatment approach to sarcoidosis were recently published however, the strength of evidence behind many of the guideline recommended drugs is weak. None of the drugs currently used for the treatment of sarcoidosis have been rigorously studied and prescription of these drugs is often based on off-label” indications informed by experience with other diseases. Indeed, only two medications (prednisone and repository corticotropin injection) currently used in the treatment of sarcoidosis are approved by the United States Food and Drug Administration. This situation results in significant reimbursement challenges especially for the more advanced (and often more effective) drugs that are favored for severe and refractory forms of disease causing an over-reliance on corticosteroids known to be associated with significant dose and duration dependent toxicities. This past decade has seen a renewed interest in developing new drugs and exploring novel therapeutic pathways for the treatment of sarcoidosis. Several of these trials are active randomized controlled trials (RCTs) designed to recruit relatively large numbers of patients with a goal to determine the safety, efficacy, and tolerability of these new molecules and therapeutic approaches. While it is an exciting time, it is also necessary to exercise caution. Resources including research dollars and most importantly, patient populations available for trials are limited and thus necessitate that several of the challenges facing drug trials and drug development in sarcoidosis are addressed. This will ensure that currently available resources are judiciously utilized. Our paper reviews the ongoing and anticipated drug trials in sarcoidosis and addresses the challenges facing these and future trials. We also review several recently completed trials and draw lessons that should be applied in future.